2017
DOI: 10.1194/jlr.m072538
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking lipid droplet-associated hydrolase, a gene linked to human prostate cancer, have normal cholesterol ester metabolism

Abstract: Lipid droplets (LDs) are cellular organelles that are important for energy and lipid metabolism (1, 2). LD accumulation is a hallmark of obesity and is linked to the metabolic syndrome and type II diabetes. LD accumulation is central to atherosclerosis development, in which macrophages in arterial walls accumulate cholesterol esters (CEs) in LDs to become foam cells. Finally, LDs accumulate in many carcinomas (3), and LDs and lipid metabolism are connected to renal clear cell carcinoma and prostate cancer (4-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Goo et al (2014) reported a CE hydrolase activity for the murine CG9186 homolog LDAH, and the characterization of one LDAH knockout mouse revealed a significantly increased body weight in female mutant mice (Currall et al, 2018), which is compatible with its function as a lipase. However, these data conflict with the analysis of a second, inde-pendent LDAH knockout mouse, whose characterization did not reveal a TAG or CE metabolism-associated phenotype (Kory et al, 2017). These data also conflict with our data concerning the knock down of CG9186 transcripts by RNAi (Thiel et al, 2013) and the analysis of the null mutant presented here (Figure 1C), both of which resulted in moderately decreased TAG storage levels in adult flies and no prominent change in the TAG storage levels in whole embryos or larvae ( Figures S1D and S1E).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Goo et al (2014) reported a CE hydrolase activity for the murine CG9186 homolog LDAH, and the characterization of one LDAH knockout mouse revealed a significantly increased body weight in female mutant mice (Currall et al, 2018), which is compatible with its function as a lipase. However, these data conflict with the analysis of a second, inde-pendent LDAH knockout mouse, whose characterization did not reveal a TAG or CE metabolism-associated phenotype (Kory et al, 2017). These data also conflict with our data concerning the knock down of CG9186 transcripts by RNAi (Thiel et al, 2013) and the analysis of the null mutant presented here (Figure 1C), both of which resulted in moderately decreased TAG storage levels in adult flies and no prominent change in the TAG storage levels in whole embryos or larvae ( Figures S1D and S1E).…”
Section: Discussionmentioning
confidence: 62%
“…For mice, the data concerning the role of LDAH in TAG storage regulation is contradictory. One LDAH knockout mouse study did not show any TAG storage differences or other prominent lipid metabolism-associated phenotypes (Kory et al, 2017). Furthermore, the authors reported negative findings from different targeted lipid modifying enzyme activity assays (Kory et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To further bolster our findings, we measured levels of oxidized phospholipids in 248 larval brains (TYURINA et al 2000;KAMAT et al 2015;KORY et al 2017). On feeding C155-249 GAL4/+ larvae with 5 mM paraquat, we enriched and detected 9 oxidized 250 polyunsaturated fatty acids (PUFAs), belonging to phosphatidylserine (PS) and 251 phosphatidylethanolamine (PE) ( Fig.…”
Section: Rosmentioning
confidence: 92%